2017
DOI: 10.1530/erc-16-0525
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA applications for prostate, ovarian and breast cancer in the era of precision medicine

Abstract: The high degree of conservation in microRNA from Caenorhabditis elegans to humans has enabled relatively rapid implementation of findings in model systems to the clinic. The convergence of the capacity for genomic screening being implemented in the prevailing precision medicine initiative and the capabilities of microRNA to address these changes holds significant promise. However, prostate, ovarian and breast cancers are heterogeneous and face issues of evolving therapeutic resistance. The transforming growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 132 publications
(168 reference statements)
0
44
0
Order By: Relevance
“…There are many recent reviews of the identity, regulation, and targets of miRNAs in BCa, e.g., (Egeland, et al 2015;Klinge 2015;Li, et al 2017c;Muluhngwi and Klinge 2015;O'Bryan, et al 2017;Smith, et al 2017;van Schooneveld, et al 2015;Yahya and Elsayed 2015). miRNAs regulate key pathways dysregulated in BCa including apoptosis, cell cycle, cellular energetics, invasion, metabolism, and metastasis.…”
Section: Mirnas In Bcamentioning
confidence: 99%
See 2 more Smart Citations
“…There are many recent reviews of the identity, regulation, and targets of miRNAs in BCa, e.g., (Egeland, et al 2015;Klinge 2015;Li, et al 2017c;Muluhngwi and Klinge 2015;O'Bryan, et al 2017;Smith, et al 2017;van Schooneveld, et al 2015;Yahya and Elsayed 2015). miRNAs regulate key pathways dysregulated in BCa including apoptosis, cell cycle, cellular energetics, invasion, metabolism, and metastasis.…”
Section: Mirnas In Bcamentioning
confidence: 99%
“…Screening of free and exosomal-associated miRNAs by high throughput sequencing platforms has identified changes in breast, ovarian, and prostate cancers (Smith et al 2017) and in thyroid cancer (Saiselet et al 2016). The release of exosomes containing miRNAs (as well as other ncRNAs, protein, and lipids) and endocytic uptake of the exosomes in recipient cells results in altered regulation of gene translation and has implicated miRNAs as hormones (reviewed in (Bayraktar, et al 2017)).…”
Section: Mirnas In Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is also contributes to epithelial-mesenchymal transition (EMT) in breast cancer (Yahya & Elsayed, 2015). TGF-β signaling pathway is capable to control and reciprocally can be controlled by multiple molecules that miRNAs seem to be one of the most noticeable of them (Smith, Agarwal, & Bhowmick, 2017). The miR-200 family frustrates the EMT process by the prevention of TGF-β signaling (Chen, Zhou et al, 2016;Pecot et al, 2013).…”
Section: Mirna: a Brief Overviewmentioning
confidence: 99%
“…Therefore, miR-191 regulates TGF-β signaling through two direct and indirect mechanisms (Nagpal et al, 2015). Recently, studies found that TGF-β pathway can also modulate miRNAs in breast tumor (Chen, Zhou et al, 2016;Smith et al, 2017). The TGF-β/SMAD4 pathway provokes promoter activity of miR-155, which in turn prompts EMT, invasion, and metastasis through the downregulation of RhoA (Kong et al, 2008).…”
Section: Mirna: a Brief Overviewmentioning
confidence: 99%